PREGNANT WOMEN WHO EXPERIENCE PSYCHOLOGICAL RESPONSES TO ANTENATAL CARE SERVICES IN MEDAN TUNTUNGAN NORTH SUMATRA: DOES SOCIOECONOMIC INFLUENCE? - Monika Br Sembiring, Serly; Br Pinem, Jeanika; Khoiriyani, Kiki; Tumanggor, Lisnawati; Br Sebayang, Amenda Paswida (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Background: Safe Motherhood consists of four pillars: family planning, antenatal care services, safe birth, and essential/emergency obstetric and neonatal care, Environmental health, the amount of knowledge of healthy living practices, the level of health care during maternity and postpartum, and the socioeconomic situations of the community.Objective: to analyze pregnant women who experience psychological responses to antenatal care services in socio-economic situations.Methods: correlation analytical research, with a cross-sectional design. The sampling technique used was purposive sampling for 1 month, which obtained up to 102 samples. This research was carried out at Medan Tuntungan North Sumatra. The independent variable was socioeconomic position, education level, location, age, work status, and anxiety, and the dependent variable was antenatal care services. Data were collected using the The instruments in this study are the Depression Anxiety Stress Scale 42 (DASS 42) The overall Cronbach’s alpha for the DASS-21 scale was 0.74. Statistical test using the Chi-Square test.Results: There is a significant related between socioeconomic position, education level, location, age, work status, and anxiety among antenatal care services. Conclusion: Pregnant women's access to antenatal care services is influenced by socioeconomic position, education level, location, age, work status, and anxiety